PEMBUATAN DAN PENGGUNAAN ALAT FILTER SAMPAH DI SALURAN AIR DESA CIBUNTU UNTUK MEWUJUDKAN LINGKUNGAN BERSIH DAN BEBAS BANJIR - Muhamad Alwi Alamsyah; Muhamad Geni Firmansyah; Nuri Abiyyah Damanhuri; Muhamad Azmi Fahrezi; Siti Nurjanah; Vynnie Fauzia; Erwin Hermawan (JPMUJ, 2024)
The research conducted in Cibuntu Village, Ciampea District, presents an innovative solution to combat environmental issues such as flooding and pollution caused by improper waste management in water channels. This initiative is manifested through the development and utilization of a Trash Filter Device (TFD). The TFD, a tangible outcome of collaborative efforts and careful planning, addresses the pressing problem of garbage accumulation within water channels, which has been a significant contributor to the recurring issue of flooding, not only in Cibuntu Village but also in many rural areas, including those in Indonesia. Floods, beyond their material losses, pose a severe threat to natural ecosystems, and thus, it is imperative to find effective and sustainable solutions to tackle garbage accumulation within these channels. The TFD offers a promising solution by intercepting and preventing waste from entering the water channels. The research process encompasses several systematic steps. It begins with a preliminary study, including the identification of water channel locations in Cibuntu Village and the collection of historical flood data. The TFD is then meticulously designed to meet the specific needs of the village, utilizing appropriate materials and technology while considering production costs and maintenance estimates. The TFD installation took place in designated water channels and underwent rigorous testing to monitor its trash-catching performance. Simultaneously, surveys were conducted among the local community to gauge their satisfaction and understanding of the TFD. The collected data, both from testing and surveys, were comprehensively analyzed to provide valuable insights and recommendations for TFD implementation and potential policy implications. This research contributes positively to addressing flood challenges and environmental pollution at the local level. By adopting the TFD technology and considering its social and economic aspects, this initiative not only presents a tangible solution but also empowers communities to actively participate in mitigating environmental issues. It is anticipated that this research will serve as a model for similar communities facing similar challenges, ultimately leading to cleaner and flood-free environments.